2012
DOI: 10.1242/jeb.060988
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent modulation of antennal sensitivity and input to antennal lobes in male moths (Spodoptera littoralis) pre-exposed to sex pheromone

Abstract: SUMMARYSex pheromones are intraspecific olfactory signals emitted by one sex to attract a potential mating partner. Behavioural responses to sex pheromones are generally highly stereotyped. However, they can be modulated by experience, as male moths previously exposed to female sex pheromone respond with a lower threshold upon further detection, even after long delays. Here, we address the question of the neural mechanisms underlying such long-term modulation. As previous work has shown increased responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 52 publications
(79 reference statements)
2
36
0
Order By: Relevance
“…In mammals oxytocin promotes a variety of social behaviors, including sexual behavior, and sexually experienced male rats have higher levels of brain oxytocin receptors as well as shorter copulation latencies compared to naïve males [7]. Prior exposure to opposite sex pheromones also can change an animal’s olfactory sensory threshold [8], [9], which may allow more rapid mate detection and increase the probability of mating success. A social environment in which there is competition for mates can have different effects on mate choice depending upon the circumstances [2], and learning via social interactions has the potential to affect sexual selection and speciation [10].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals oxytocin promotes a variety of social behaviors, including sexual behavior, and sexually experienced male rats have higher levels of brain oxytocin receptors as well as shorter copulation latencies compared to naïve males [7]. Prior exposure to opposite sex pheromones also can change an animal’s olfactory sensory threshold [8], [9], which may allow more rapid mate detection and increase the probability of mating success. A social environment in which there is competition for mates can have different effects on mate choice depending upon the circumstances [2], and learning via social interactions has the potential to affect sexual selection and speciation [10].…”
Section: Introductionmentioning
confidence: 99%
“…In S . littoralis , pre-exposure experiments and behavioural pheromone tests were performed only with sexually mature 2- to 3-day-old males and it was suggested that pre-exposure elicits a sensitization to the pheromone by enhancing peripheral and central neuron sensitivity [25, 26, 28, 39]. Here we show that the behavioural pheromone pre-exposure effect is age-independent in A .…”
Section: Discussionmentioning
confidence: 52%
“…Such a type of olfactory plasticity based on non-associative learning has been unveiled in the moth Spodoptera littoralis : a brief pre-exposure to sex pheromone enhances behavioural responses to sex pheromone 15 min and 24 h later [25, 26]. Pheromone exposure was also shown to enhance peripheral pheromone detection, central nervous pheromone responses, and to induce an increase in the volume of certain glomeruli and specifically the size of the biggest glomerulus processing the main pheromone component within the antennal lobe (AL), the primary olfactory centre, as well as in a secondary olfactory centre, the calyces of the mushroom bodies [25, 27, 28]. It is so far unknown if such pre-exposure effects are also present in other insects and if they depend on the physiological state of the insect.…”
Section: Introductionmentioning
confidence: 99%
“…Plasticity in olfactory pathway responsiveness can be an underlying factor that modulates behavioral variation over the course of an individual's life (Davis and Takahashi 1980;Davis 1984;Gadenne and Anton 2000;Gadenne et al 2001;Anderson et al 2007;Anton et al 2007; Barrozo et al 2010Barrozo et al , 2011George et al 2011;Guerrieri et al 2012;Cator et al 2013). Plasticity in the response to chemosensory cues can ensure appropriate, context-dependent responses, i.e., only responding to sex pheromones at certain times of the day or night or otherwise only when capable of mating (Shorey et al 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory cues are detected, processed and classified by the olfactory system, which is similarly modularly organized in both vertebrates and invertebrates (Hansson 1999;Wyatt 2014). Modulation of behavioral responses to olfactory cues can be driven by alterations in the sensitivity of olfactory sensory neurons (OSNs) in the peripheral nervous system, as in flies and mosquitoes (Davis and Takahashi 1980;Davis 1984;Crnjar et al 1990;George et al 2011;Cator et al 2013) or noctuid moths (Anderson et al 2007; Barrozo et al 2011;Guerrieri et al 2012). Alterations can also occur in the central nervous system, during the processing and integration of odorant cue information in the antennal lobe and its neurons projecting to protocerebral neuropils, such as occurs in the moth, Agrotis ipsilon (Gadenne and Anton 2000;Gadenne et al 2001).…”
Section: Introductionmentioning
confidence: 99%